Teaching Education and Socio-educational Action: Developing an Implementation Proposal of the Program Community Teachers (PCT) - Barberousse-Alfonso, Paulette (2018)
From a critical and transformative approach, this essay presents inputs and relevant conclusions obtained during the first stage of the project Construyendo una propuesta de implementación del Programa Maestros Comunitarios (PMC), Code number 0166-15 DEB-UNA (UNA, DEB, s. f.), conducted in 2016. Considering our perspective as researchers and professors at División de Educación Básica, the paper addresses a current topic within the socio-educative field to face challenges of contemporary educational models in formal and non-formal areas of elementary education in the Costa Rican context. Our purpose is that students and teachers of the career program Pedagogía con énfasis en I y II ciclos de la Educación General Básica have an overview of the national, social, and educational reality in an attempt to involve them in applying pedagogical actions towards finding a solution to school dropouts at Escuela Finca Guararí, Heredia, Costa Rica. The essay describes the experience of teaching education students and their socio-educational action with the focus on the systematization of the experience in the initial stage of the project. Furthermore, the paper connects with emerging strategic knowledge areas at División de Educación Básica (DEB), such as social and community pedagogy in the context of the National University (UNA) of Costa Rica. It takes over a route already traced at DEB, which proposes more flexible and alternative pedagogic formats to promote educational equity and diversity issues. The paper describes the project background and a theoretical framework, as well as aspects that have been shared by the protagonist actors along the process: students-teachers, host teachers, supervisor professors, school children, and their parents at Escuela Finca Guararí. Conclusions address main results and facts during 2016 in order to show the viability of the project, which is conducted from a public university. Finally, the article also includes an overview of the project’s future in terms of its implementation in the Costa Rican context.